PROSES DESAIN PRODUK SNEAKERS KOLABORATIF DALAM NEGERI: STUDI KASUS KOLABORASI MEREK A DENGAN GRUP MUSIK SK - Celvin Tauhid Allraysa (Fakultas Seni Rupa dan Desain ITB, 2021)
This research is a case study that discusses collaborative products between brand A and the SK music group. Thisresearch uses qualitative method where data collection was carried out by interviewing the manufacturers of sneakersA to find out the relationship between the products and the design process carried out on the collaboration. The resultsobtained are in the form of a design process from a manufacturer of sneakers A and the role of collaborators in eachstage of the design process. The analysis is in the form of a comparison between the data obtained from the interviews and from the literature used. From the research results, it was found that there were differences in the types of sneakers in the collaborative product series, and some of the designs did not match the image of the collaborators who were personnel of the rock music group SK. This research is expected to be a recommendation for producers and designers in designing collaborative products. In the academic field, it is also expected to open new research related to collaborative sneakers and other collaborative products.